2000
DOI: 10.1073/pnas.120074297
|View full text |Cite
|
Sign up to set email alerts
|

A role of transcriptional activators as antirepressors for the autoinhibitory activity of TATA box binding of transcription factor IID

Abstract: . 2). An alternative model postulates that the holoenzyme enters the preinitiation complex as a preassembled unit (2, 3). Although the nature of the assembly pathway most relevant to the in vivo context remains unclear, access of TFIID to the core promoter is likely to be a critical step in any pathway, given that only TFIID binds to the promoter in a sequence-specific manner. In support of this view, in vitro recruitment experiments using immobilized promoters demonstrated that the holoenzyme is not recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 43 publications
8
75
0
Order By: Relevance
“…Indeed, Nakatani and colleagues (27) found that a fragment of dTAF250p competed with the VP16 activation domain for interaction with specific amino acid sequences on the concave surface of TBP. These data are consistent with their hypothesis that the TAF130p TAND domain and transactivators compete with DNA for interactions on TBP's DNA binding surface (79). This continuous negative action of the TAND may be antagonized, or derepressed, by the action of TFIIA (Refs.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, Nakatani and colleagues (27) found that a fragment of dTAF250p competed with the VP16 activation domain for interaction with specific amino acid sequences on the concave surface of TBP. These data are consistent with their hypothesis that the TAF130p TAND domain and transactivators compete with DNA for interactions on TBP's DNA binding surface (79). This continuous negative action of the TAND may be antagonized, or derepressed, by the action of TFIIA (Refs.…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that the VP16 activation domain may not interact with TBP and TFIIB in the context of a preinitiation complex, and in this regard our observed crosslinking occurs primarily (and perhaps exclusively) when the proteins are not bound to DNA. Our results are consistent with the idea that activation domains can function as antirepressors of the autoinhibitory activity of TBP (65). However, while our results establish that the VP16 activation domain directly interacts with TBP and TFIIB in vivo, the importance of these interactions for transcriptional activity in vivo remain to be determined.…”
Section: Figsupporting
confidence: 81%
“…First, unlike the case for SAGA, TBP and TFIIB are not recruited by the Gal4 activator bound to its genomic sites in the absence of a TATA element (23,24). Second, the VP16 activation domain interacts with surfaces of TBP (64,65) and TFIIB (31,66) that are critical for promoter binding, and mutations that abolish the interactions in vitro do not significantly affect the level of transcriptional activity in vivo (67,68). This suggests that the VP16 activation domain may not interact with TBP and TFIIB in the context of a preinitiation complex, and in this regard our observed crosslinking occurs primarily (and perhaps exclusively) when the proteins are not bound to DNA.…”
Section: Figmentioning
confidence: 99%
“…In vivo cross-linking experiments have shown clearly that TBP does not associate with the TATA box of the GAL1 promoter until Gal4p activity has been induced (12,13), so Gal4p either directly or indirectly plays an important role in this event. Since many inhibitors of TBP-TATA interactions are known (28, 36 -40), one model is that the activator could help to compete these negative regulators from TBP and then "hand-off" the protein to the TATA box (41). This type of model would be consistent with the inability of TBP to bind Gal4p and DNA simultaneously as well as the in vivo cross-linking result.…”
Section: Gal4p-tbp-dna Interactionssupporting
confidence: 53%